Pengaruh Latihan Sirkuit Terhadap Kemampuan Teknik Dasar Pembelajaran Permainan Bola Voli Siswa Sekolah Menengah Pertama - Agrilia Damayanti S.P; Febi Kurniawan; Ega Trisna Rahayu (Peneliti.net, 2022)
The purpose of this study was to determine the effect of circuit training on the basic technical skills of learning volleyball games at SMPN 2 Telukjambe Timur. To find out whether there is an effect of circuit training on the ability of the basic techniques of learning volleyball games. The research method used in this study is the experimental method. The design or design in this study uses one group pretest posttest design. The population in this study were 440 students. The sample selection used cluster random sampling by conducting a random lottery with a total sample of 44 students. The results of the paired sample t-test in the experimental group showed significant results of 0.000 and a mean pretest value of 10.68 and a posttest mean value of 16.36 and a gain score of 0.0635 that there was an increase, so it can be concluded that circuit training on basic volleyball game technical skills in PJOK learning improves basic technical skills of underpassing, overpassing, underhand serve, overhand serve and volleyball smash.